2022
DOI: 10.17533/udea.hm.v13n2a03
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Carbapenem Inactivation Method (mCIM): Highly sensitive and specific low-cost tool to assess carbapenemase-producing and non-producing in Gram-negative bacilli

Abstract: Introduction: Carbapenemase-producing Gram-negative bacilli is a worldwide problem, which represent a health concern, because most of its resistance mechanisms are encoded by plasmids, therefore easily transmissible in hospital settings. Many methods have been proposed to detect such resistance, but screening is still challenging, recently the modified carbapenem inactivation method has shown promising results, however more studies need to be performed. Hence, this study aimed to evaluate the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…This was particularly true for metallo β-lactamases, with 96% mCIM positivity (i.e., 234 out of 240 were positive for EDTA-carbapenem inactivation method (eCIM). This is consistent with a study by Gallego et al, which showed that the prevalence of mCIM was between 96% and 98% [ 8 ]. A study in Lucknow by Rahman et al recorded a 100% prevalence of NDM genes in all the carbapenem-resistant Enterobacterales [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…This was particularly true for metallo β-lactamases, with 96% mCIM positivity (i.e., 234 out of 240 were positive for EDTA-carbapenem inactivation method (eCIM). This is consistent with a study by Gallego et al, which showed that the prevalence of mCIM was between 96% and 98% [ 8 ]. A study in Lucknow by Rahman et al recorded a 100% prevalence of NDM genes in all the carbapenem-resistant Enterobacterales [ 9 ].…”
Section: Discussionsupporting
confidence: 93%